2015
DOI: 10.1177/0394632015600534
|View full text |Cite
|
Sign up to set email alerts
|

Labeling quality and molecular characterization studies of products containing Lactobacillus spp. strains.

Abstract: The objective of the study was to characterize at species level by phenotypic and different molecular methods the strains of Lactobacillus spp. used as constituents of five oral and four vaginal products. Susceptibilities to representative antibiotics were evaluated. In addition, total viable counts at mid and 3 months to deadline of shelf life, in the different formulations and the presence of eventual contaminant microorganisms were investigated. In all oral products the molecular characterization at species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…They also confirmed that the 16S rRNA gene sequence was inadequate for distinguishing between species in the L. casei group. The misidentification of a commercial L. casei strain (DG, CNCM I-1572) found in an Italian pharmaceutical product was also reported by Blandino et al (2016) , who successfully used multiplex PCR based on tuf gene amplification ( Blandino et al, 2016 ).…”
Section: Discussionmentioning
confidence: 72%
“…They also confirmed that the 16S rRNA gene sequence was inadequate for distinguishing between species in the L. casei group. The misidentification of a commercial L. casei strain (DG, CNCM I-1572) found in an Italian pharmaceutical product was also reported by Blandino et al (2016) , who successfully used multiplex PCR based on tuf gene amplification ( Blandino et al, 2016 ).…”
Section: Discussionmentioning
confidence: 72%
“…The authors found that all products contained L. crispatus by culture-independent methods, but only six formulations carried living cells (Di Pierro et al, 2019). The identification of species declared to be contained in five Italian oral products revealed concordant microbial composition to the label claims for four formulations (Blandino et al, 2016). Identification of species contained in 13 French functional foods by MALDI-TOF MS, PCR and sequencing of tuf and 16S rRNA genes revealed different species than those stated for two products (Angelakis et al, 2011).…”
Section: Microbial Compositionmentioning
confidence: 95%
“…An incongruent microbial amount was found in 5 among 10 investigated European products ( Coeuret et al, 2004 ). Thirty among 46 analyzed Italian products contained the amount of living microbes declared on the labels ( Aureli et al, 2010 ; Blandino et al, 2016 ). Among 24 Italian products tested by Toscano et al (2013) , 10 were found to contain an incorrect amount of cells.…”
Section: Compositional Qualitymentioning
confidence: 99%
“…This was, for instance, an issue in the context of probiotic supplements where it was found that ingredient lists occasionally do not correspond to the microorganisms present in the products (e.g. Lewis et al 2016, Blandino et al 2016.…”
Section: Taxonomic Identification Of Microorganisms Usedmentioning
confidence: 99%